Kebijakan Travel Bubble Indonesia Dan Singapura Dalam Upaya Pemulihan Sektor Pariwisata Di Era COVID-19 - Latifah, Fani Rahmah; Rizwani, Nurul Febria (JURNAL DESTINASI PARIWISATA; Vol 11 No 2 (2023): VOL 11, NO 2 (2023): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2023.v11.i02.p27, 2023)
Tourism is one of the sectors most affected by the widespread transmission of the Covid-19 virus. This occurs as a result of the implementation of various policies that limit the space for economic and tourism activities. However, to continue running the tourism sector amidst the implementation of restrictive policies, the government has implemented a policy, namely "Travel Bubble", which is implemented based on a bilateral agreement between countries to facilitate entry and exit services between collaborating countries so that foreign tourists can visit Indonesia without having to carry out strict quarantine. The main aim of this research is to see how the Travel Bubble is implemented in Indonesia and its effectiveness in increasing foreign tourist visits. Data was collected through document searches. Keywords: tourism, Covid-19, government, travel bubble